2002
DOI: 10.1007/s004050100407
|View full text |Cite
|
Sign up to set email alerts
|

Avian dark cells

Abstract: Dark cells (DCs) of mammalian and non-mammalian species help to maintain the homeostasis of the inner ear fluids in vivo. Although the avian cochlea is straight and the mammalian cochlea is coiled, no significant difference in the morphology and/or function of mammalian and avian DCs has been reported. The mammalian equivalent of avian DCs are marginal cells and are located in the stria vascularis along a bony sheet. Avian DCs hang free from the tegmentum vasculosum (TV) of the avian lagena between the perilym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 88 publications
(117 reference statements)
0
5
0
Order By: Relevance
“…Of the 11 spinning cells we identified in the lagena and basilar papilla in our initial screen, 6 had a very distinct broccoli-shape morphology. TEM analysis revealed that these cells have a subcellular architecture consistent with dark cells, which are found in the extensively vascularized tegmentum vasculosum (31). Dark cells, which are believed to play a role in endolymph generation, have an electron-dense organelle-rich cytoplasm, which is expanded basally by extensive membrane infoldings (Fig.…”
Section: Discussionmentioning
confidence: 79%
“…Of the 11 spinning cells we identified in the lagena and basilar papilla in our initial screen, 6 had a very distinct broccoli-shape morphology. TEM analysis revealed that these cells have a subcellular architecture consistent with dark cells, which are found in the extensively vascularized tegmentum vasculosum (31). Dark cells, which are believed to play a role in endolymph generation, have an electron-dense organelle-rich cytoplasm, which is expanded basally by extensive membrane infoldings (Fig.…”
Section: Discussionmentioning
confidence: 79%
“…This localization has been attributed to the maintenance of the Na + –K + gradient across the cytosol and nucleus [ 156 ]. Ouabain-sensitive Na + , K + -ATPase localization in animal systems has revealed a general distribution of the enzyme as evident from a diffuse blue fluorescence in the cells [ 157 ]. Ouabain-sensitive ATPase activity in Halocnemum sp.…”
Section: Salt Stress-induced Modulation Of Ouabain-sensitive Atpamentioning
confidence: 99%
“…This loss in the EP paralleled the damage and repair of the dark cells of the tegmentum vasculosum that are responsible for the secretion of potassium into the scala media [Hara et al, 2002;Ramakrishna et al, 2004]. In the adult chicken, there is little evidence of a transient EP loss just after exposure to intense sound [Trautwein et al, 1997].…”
Section: Introductionmentioning
confidence: 99%